Deconstructing the Language of Accounting Textbooks to Make Power Relations Visible - Irsyadillah Irsyadillah; Ruaida Ruaida; Musfiana Musfiana (Jurnal Dinamika Akuntansi dan Bisnis, 2021)
The paper is motivated by the realization of the absent of critical engagement research problematizing the mainstream accounting worldview within accounting textbooks in the context of Indonesia. By doing so, this study uses the Thompson’s (1990) Schema of analyzing ideology to examine the content of popular introductory financial accounting (IFA) textbooks adopted by universities to reveal how, and the extent to which, the ideological status quo is reflected within these texts. This means the analysis tries to understand how ideological meaning is constructed within the textbooks. The analysis shows that the investigated textbooks portray accounting as an abstracted notion of a practical and calculative tool. Meanwhile, the ideological assumptions and socio-political and cultural background and conflict inherent in accounting are concealed and obscured. The textbooks have not scrutinized the concepts and measurement of accounting beyond employing a shareholder perspective. Consequently, the users’ attention is deflected from or glossed over the underlying ideological nature of the textbooks